Practical skill development in new nurses - Torunn Bjørk, Ida (Nursing Inquiry, 1999)
This paper reports the results of an empirical study of new nurses’ development of practical skill. Actual practice and clinical learning of new nurses has received minor attention in nursing research. This may build on the assumption that practical skill naturally improve as a result of working in the clinical setting. In the present study nurses were videotaped several times as they performed in the clinical setting, and interviewed after each filming. Analysis of skill development was rendered possible by comparing characteristics of performance over time. A model of practical skill performance was developed during the analysis. This model advances a broader understanding of practical skill by incorporating the following constructs: substance and sequence, accuracy, fluency, integration and caring comportment. The nurses’ trajectories of practical skill development are presented on the basis of this model. Individual and common trends in practical skill development are discussed, and the idea of development of practical skill as a natural happening in the clinical setting is critiqued.
Keywords: clinical competence; graduate nurse; learning; nursing skills; skill acquisition; video-recording